Factors influencing archaeological tourists' behavioral intentions: a conceptual framework - Pong, Kok Shiong; Abdullah, Abdul Rashid (Penerbit Universiti Teknologi MARA (UiTM) Malaysia, 2017)
Archaeological tourism has tremendous potential to lure inbound and outbound tourists with the announcement of Lenggong Valley as a World Heritage Site in 2012. Promoting archaeological tourism needs extra effort since the public has limited idea of what the site can offer. Therefore, a series of strategies need to be developed to attract more tourists to archaeological sites. This study assesses the literature on the causal effect of destination personality, satisfaction, and behavioral intentions among tourists who visit the archaeological sites. A conceptual framework was developed based on the literature propositions. This study contributes to the tourism literature by being one of the primary works in applying destination personality concept on archaeological sites. Furthermore, the findings of the research are anticipated to provide recommendations from the demand side which usually lacking for local authorities and destination marketing organizations’ in their branding and positioning strategies for destinations.